1971
DOI: 10.1073/pnas.68.12.3045
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G and Free Kappa-Chain Synthesis in Different Clones of a Hybrid Cell Line

Abstract: ABSTRACT13 clonal cell lines were isolated from a hybrid cell population established by cell fusion between cloned BALB/c myeloma cells that were resistant to 8-azaguanine and produced immunoglobulin G and free kappa chain and Cs7BL/6n lymphoma cells that were resistant to bromodeoxyuridine and did not produce immunoglobulins. Some of the histocompatibility-2 antigens of both parental cell lines could be demonstrated on all of the hybrid clones. 11 clones synthesized only free kappa chain. Two clones synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…5 In patients in whom both intact immunoglobulin and light chain are secreted, it is assumed that they originate in different MM plasma cell clones with different levels of differentiation. 6 In fact, in the course of MM progression especially with multiple relapses, dedifferentiation is frequently observed, characterized by "Bence Jones escape," cessation of M-protein secretion, or "high-grade transformation" (best captured by increased levels of serum lactate dehydrogenase [LDH]). 7,8 The elusive MM stem cell is thought to have a pre-plasma cell phenotype incapable of immunoglobulin secretion, 9 although others have shown that the terminally differentiated plasma cell retained self-renewal potential, 10 consistent with the recent notion of stem cell plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…5 In patients in whom both intact immunoglobulin and light chain are secreted, it is assumed that they originate in different MM plasma cell clones with different levels of differentiation. 6 In fact, in the course of MM progression especially with multiple relapses, dedifferentiation is frequently observed, characterized by "Bence Jones escape," cessation of M-protein secretion, or "high-grade transformation" (best captured by increased levels of serum lactate dehydrogenase [LDH]). 7,8 The elusive MM stem cell is thought to have a pre-plasma cell phenotype incapable of immunoglobulin secretion, 9 although others have shown that the terminally differentiated plasma cell retained self-renewal potential, 10 consistent with the recent notion of stem cell plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of mouse hepatoma cells with human leukocytes resulted in the induction of human albumin production (31). Attempts to induce immunoglobulin production (17,(32)(33)(34)(35)(36) have failed. However, fusion of two parental cells capable of producing immunoglobulin has permitted continued immunogiobulin production (11,17,32,34).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to induce immunoglobulin production (17,(32)(33)(34)(35)(36) have failed. However, fusion of two parental cells capable of producing immunoglobulin has permitted continued immunogiobulin production (11,17,32,34).…”
Section: Resultsmentioning
confidence: 99%